Mechanisms underlying obesity-related insulin resistance - Tewari, Nilanjana (2016)
This thesis investigates the effect of body composition on insulin resistance and the impact of supplementation with nutritional support or carbohydrate treatment. Insulin resistance occurs as a response to a number of stressors, including surgery. However, the mechanism underlying the development of insulin resistance is as yet unclear. Adipose tissue distribution appears to play a role in the development of insulin resistance and obesity-related complications.